Tingkat Kelengkapan Rekam Medis di Puskesmas I Denpasar Timur : Pendekatan Kuantitatif - Indraswari, Made Ayu Savitri; Adiputra, I Made Sudarma; Faidah, Nurul (Jurnal Akademika Baiturrahim Jambi, 2025)
Medical records are essential documents that serve as a means of communication among healthcare professionals and form the basis for service planning, evaluation, and legal evidence within the healthcare system. The completeness of medical record documentation is a key indicator in ensuring the quality of healthcare services. This study aims to analyze the completeness level of outpatient medical records at UPTD Puskesmas I, East Denpasar District Health Office. A quantitative descriptive approach was used with random sampling techniques applied to 372 medical record files out of a total population of 5,251. Data collection was conducted using a checklist that assessed four main aspects: patient identification, essential reports, authentication, and proper documentation. The data were analyzed using univariate analysis. The results showed that the average completeness for patient identification was 67.3%, essential reports 95.38%, authentication 50%, and documentation 100%. Overall, the completeness of medical records has not fully met the established standards, particularly in legal and administrative aspects. This incompleteness may lead to serious consequences, such as errors in medical service delivery, weak legal accountability, and reduced quality of healthcare services. Therefore, this study highlights the need to strengthen internal supervision, conduct regular training for healthcare workers on proper medical record documentation, and implement routine evaluations to improve service quality and regulatory compliance